CRITICAL COMPONENT DETERMINATION ANALYSIS ON DIESEL GENERATOR CATERPILLAR TYPE 3412C WITH RELIABILITY METHOD - Ponidi, Ponidi (Lembaga Penelitian Dan Pengabdian Kepada Masyarakat Universitas 17 Agustus 1945 Surabaya, 2019)
Diesel generators are aircraft that are very important for the smooth operation of a ship.Diesel generator functions as a source of electrical voltage. So that if it is damaged, all aircrafton the ship that require electricity do not work and the ship is not likely to operate. With thepassage of time, the diesel generator will certainly not escape damage, both minor damage andheavy damage. One of them is the damage that occurs in the Diesel Generator IV Caterpillartype 3412 C owned by KRI Ahmad Yani-351 in the Koarmada II area of Surabaya. With thisresearch, an analysis of damaged diesel generator components will be carried out. The damagedata is obtained from the company providing diesel generator repair services, namely PT. TescoIndomaritim or damage journal from the ship to be analyzed by FMECA (Failure Modes Effect& CriticalÂ Analysis) method and reliability method with weibull ++ 6. After analyzing, themost critical component of the diesel generator is obtained, namely in the Piston Ring which isknown as the reliability value equal to 0.578026, Probability of failure equals 5.7791E-05 andFailure rate is 9 , 9980E-05 with the weibull ++ 6 software.Keywords : Time to failure(TTF),Weibull ++6, FMECA